A new Late Cretaceous genus and species of polypore fungus beetles (Coleoptera, Tetratomidae) from northern Myanmar. (31st December 2016) - Yu, Yali; Hsiao, Yun; Ślipiński, Adam; Jin, Jianhua; Ren, Dong; Pang, Hong
Abstract: A new polypore fungus beetle is described and illustrated, under the name of Thescelostrophus cretaceus gen. et sp. nov., representing the first documented occurrence of the tribe Eustrophini. The well-preserved specimen was collected from the Upper Cretaceous (Cenomanian, ca. 99 Ma) amber near the Hukawng Valley of northern Myanmar. This fossil species can be assigned to the extant subfamily Eustrophinae based on its elongate oval and strongly narrowed posteriorly body, simple and narrow tarsi, and somewhat clubbed antennomeres. The comparison among the extinct and extant eustrophines supports the previous hypothesis that antennal morphology of early eustrophines was very diverse. Additionally, an overall similarity between Thescelostrophus and extant eustrophines suggests a potential fungivory of this fossil species. Morphological characters preserved in the Burmese amber highlight the diversity of tetratomids during the Late Mesozoic and provide data for future phylogenetic studies of Tetratomidae.